2018
DOI: 10.1111/geoj.12262
|View full text |Cite
|
Sign up to set email alerts
|

What defines a river? Modelling the interplay between physical and social driving factors in characterising the waterways in Chile

Abstract: The categorisation of natural landscape features places a socialised and ordered lens on the landscape. In the case of natural waterways, it creates a regional hydrological vocabulary, based on physical processes and cultural history. This study uses the unique combination of hydrological and cultural characteristics found in Chile to determine the degree to which local waterway classifications of waterways as rivers (río in Spanish) provide insights into the cultural role in perceiving and describing such imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, in the absence of spatially distributed information on hydrological regime and sediment transport dynamics, the name given to waterways can help shedding light on the processes mediated by the local cultural context. Lacy et al (2018) analyzed the way waterways are named in Chile, and found that this is due to a unique combination of hydrological characteristics and cultural perspectives, quebrada being generally used to refer to intermittent waterways, estero as a small stream or creek, and río a perennial waterway, irrespective of the size. The aim of this article is to review recent research into the fluvial geomorphological and ecological nature of the Silala River in the North of Chile, and will deal with (i) the characterization of the fluvial nature of the forms featured in the main channel; (ii) the characterization of the fluvial nature of the sediment mobility and transport processes; and (iii) the analysis of the main ecological characteristics of the river, and particularly the fish population.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the absence of spatially distributed information on hydrological regime and sediment transport dynamics, the name given to waterways can help shedding light on the processes mediated by the local cultural context. Lacy et al (2018) analyzed the way waterways are named in Chile, and found that this is due to a unique combination of hydrological characteristics and cultural perspectives, quebrada being generally used to refer to intermittent waterways, estero as a small stream or creek, and río a perennial waterway, irrespective of the size. The aim of this article is to review recent research into the fluvial geomorphological and ecological nature of the Silala River in the North of Chile, and will deal with (i) the characterization of the fluvial nature of the forms featured in the main channel; (ii) the characterization of the fluvial nature of the sediment mobility and transport processes; and (iii) the analysis of the main ecological characteristics of the river, and particularly the fish population.…”
Section: Introductionmentioning
confidence: 99%